2008
DOI: 10.1017/s0317167100009409
|View full text |Cite
|
Sign up to set email alerts
|

Intraspinal Neurenteric Cysts in Children

Abstract: Background:Neurenteric cysts are rare congenital epithelium-lined cysts of the central nervous system. They are found predominantly in the spinal cord, with lower incidence in the intracranial compartment, and may be associated with various other congenital spinal anomalies. Seven patients with symptomatic intraspinal neurenteric cysts are presented.Materials and Methods:Seven patients with intraspinal neurenteric cysts aged from nine months to ten years treated at this hospital from May 2000 to July 2006 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 24 publications
0
42
0
4
Order By: Relevance
“…MRI is now the main diagnostic modality of choice for patients with spinal symptoms [17]. It provides greater anatomic detail, offers more information about bone and soft tissue involvement, and potentially characterizes the tissue of the tumor mass itself.…”
Section: Discussionmentioning
confidence: 99%
“…MRI is now the main diagnostic modality of choice for patients with spinal symptoms [17]. It provides greater anatomic detail, offers more information about bone and soft tissue involvement, and potentially characterizes the tissue of the tumor mass itself.…”
Section: Discussionmentioning
confidence: 99%
“…10,[20][21][22]25,[32][33][34][37][38][39] In 4 infants, they presented as a meningitis-like syndrome, probably resulting from rupture of the cyst into the subarachnoid space. 8,14,19,26,40 Although commonly associated with other abnormalities, intraspinal NECs may be found without any abnormalities, and bone abnormalities were found in only 8 patients (21.1%) with an intramedullary NEC. 3,18,19,21,24,37,[40][41][42] Surgical methods ranged from cyst puncture and aspiration 25,39 to resection with cyst marsupialization or cyst-subarachnoid shunting.…”
Section: Follow-upmentioning
confidence: 99%
“…The GTR rates for IDEM NECs in the literature range from 71% to 75%. 8,10,12 However, GTR is not feasible for intramedullary NECs. In 8 cases in the present study, the cyst wall showed no adhesion to the spinal cord, and GTR was achieved by using microsurgical techniques.…”
Section: Diagnosis and Differentiationmentioning
confidence: 99%
See 2 more Smart Citations